Development of a short questionnaire to assess physical activity among adolescents - Kannan Aishwarya; Vetri Selvakumar; Anushya Selvakumari; Gopichandran Vijayaprasad (Wolters Kluwer Medknow Publications, 2017)
Background: Sedentary life style is a major risk factor for non-communicable diseases. There has been increasing reports of reduced physical activity among adolescents in recent times. There is a need to clinically assess levels of physical activity among adolescents. Objective: To develop a short three item scale for measuring physical activity among adolescents and check its validity and reliability. Methods: A cross sectional study was conducted on a sample of 200 students aged 13-16 years, selected from a school in Chennai using a random sampling method stratified by sex and class of study. A short three item questionnaire covering the domains of transportation to school, physically active playing during leisure time and time spent in sleep was developed with a Likert type response format based on frequency of the activity. The short physical activity questionnaire and the General Physical Activity Questionnaire (GPAQ) were administered to the adolescents. The same questionnaires were administered to the adolescents after 2 weeks. Intra class Correlation was assessed to check reliability of the measure and Pearson's Correlation to check for validity of the short physical activity scale compared to GPAQ. Results: The students had a mean score of 9.57 (SD 2.39) out of a maximum score of 15 in the short physical activity scale. The short physical activity score showed good reliability with intra class correlation of 0.770 (95% CI 0.686 - 0.831). There was a statistically significant correlation between the short physical activity scale score and the METS calculated from the GPAQ with a Pearson's correlation of 0.232 (p = 0.002). Conclusions: The short physical activity scale has an acceptable validity and good reliability in measuring physical activity level among adolescent students.